2006
DOI: 10.1038/sj.ejcn.1602457
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of crying episodes owing to infantile colic: a randomized controlled study on the efficacy of a new infant formula

Abstract: Objectives: The aim of this study was to evaluate the efficacy on crying episodes owing to infantile colic of a new infant formula containing partially hydrolysed whey proteins, prebiotic oligosaccharides (OS), with a high b-palmitic acid content. Design: Prospective randomized controlled study. Setting: Italy. Subjects: Two hundred and sixty-seven formula-fed infants, aged less than 4 months, with infantile colic, were randomized to receive either the new infant formula (study treatment (ST)) or a standard fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 34 publications
1
74
0
11
Order By: Relevance
“…Clinical studies have focused mostly on the efficacy of Lactobacillus reuteri, which seemed useful for the treatment of breastfed infants suffering from infantile colic (16,(27)(28)(29)(30). So far, based on recent advances in the role of galacto-oligosaccharides, modulation of gut microbiota with probiotics, prebiotics or fermented dairy products has been proposed and some clinical trials have been performed (14). A clinical and microbiological study also showed that prebiotic-supplemented formula promoted Bifidobacterium and Lactobacillus growth and inhibited Clostridium growth, resulting in a significantly lower occurrence of colic (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have focused mostly on the efficacy of Lactobacillus reuteri, which seemed useful for the treatment of breastfed infants suffering from infantile colic (16,(27)(28)(29)(30). So far, based on recent advances in the role of galacto-oligosaccharides, modulation of gut microbiota with probiotics, prebiotics or fermented dairy products has been proposed and some clinical trials have been performed (14). A clinical and microbiological study also showed that prebiotic-supplemented formula promoted Bifidobacterium and Lactobacillus growth and inhibited Clostridium growth, resulting in a significantly lower occurrence of colic (31).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the optimal composition of infant formula for infants affected by colic is based on protein hydrolysates, low lactose content, prebiotics and/or probiotics, although scientific evidence that supports this approach remains limited (14). In particular, probiotics and prebiotics have gained great interest in the field of infant nutrition after the discovery of indigestible oligosaccharides in human milk, which contribute to shape the intestinal microbiota of newborns.…”
Section: Key Notesmentioning
confidence: 99%
“…This study confirms the beneficial effect in a population of children with colic. Noteworthy, the formula also contained probiotics, for which a potential contribution to a better GI tolerance may be considered : infants with colic were successfully handled with formulae containing, among others, prebiotic oligosaccharides (Savino et al, 2006) or Lactobacillus reuteri .…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms typically start in the second week of life, in both breastfed and formula-fed infants, and usually resolve by three months of age (Lucas 1998). Generally speaking, these symptoms are not indicative of disease, and thus hospital admission for these infants is generally unnecessary, detrimental, and not to be encouraged (Savino 2007a). However, about 5% of colicky, crying infants do have a serious, underlying medical problem (Freedman 2009;Savino 2007a), and there is evidence that older children presenting with migraine are more likely to have been babies who had suffered colic (Romanello 2013).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…Generally speaking, these symptoms are not indicative of disease, and thus hospital admission for these infants is generally unnecessary, detrimental, and not to be encouraged (Savino 2007a). However, about 5% of colicky, crying infants do have a serious, underlying medical problem (Freedman 2009;Savino 2007a), and there is evidence that older children presenting with migraine are more likely to have been babies who had suffered colic (Romanello 2013). Therefore, all colicky infants should undergo a complete medical assessment in order to exclude underlying medical conditions that require investigation and treatment (Savino 2010a).…”
Section: Description Of the Conditionmentioning
confidence: 99%